Reasons for Joining, Anticipated Benefits, Stages and Procedures of the Implementation of Bologna Reforms in the Higher Education System of the Republic Of Moldova - Sitari, Daniela (Acta Universitatis Danubius. Relationes Internationales, 2023)
The Bologna reform is a process of harmonizing higher education systems in Europe, which aims to improve the quality of higher education, facilitate the mobility of students and teaching staff, as well as increase the attractiveness of European higher education worldwide. The Republic of Moldova adopted and started to implement this reform in its higher education system. The Republic of Moldova adopted the necessary legislation to implement the Bologna process. This includes the adoption of the bachelor's, master's and doctorate curriculum, as well as the establishment of quality assurance standards. The implementation of the Bologna reforms is a complex and long-term process, but it can bring many benefits for the higher education system in the Republic of Moldova and for the participants in this system.